Numerical investigation of the stagnating laminar premixed methane/air flame with fuel concentration oscillation using a four-step reaction mechanism - Sotaro MIYAMAE (The Japan Society of Mechanical Engineers, 2014)
Responses of stagnating laminar methane/air premixed flames under fuel concentration oscillation, i.c., equivalence ratio oscillation, were numerically investigated using a one-step overall reaction mechanism and a four-step reaction mechanism that included CO and H2 formation. The flame motion was numerically investigated for three different oscillation cases namely: lean, rich and lean-rich crossover case. Methane/air mixtures with sinusoidal equivalence ratio oscillations were issued from the burner exit with uniform 1.0 m/s velocity profiles. In the steady state condition, the one-step overall reaction mechanism and the four-step reaction mechanism had nearly the same characteristics in the lean region, while in the rich region variations in characteristics such as flame location and flame displacement speed for the four-step model were much more significant than those for one-step model. When the equivalence ratio was oscillated, the flame location oscillated. The amplitude of the flame location oscillation did not change with the equivalence ratio oscillation when the frequency of equivalence ratio oscillation was less than 8Hz, while it decreased monotonically when it exceeded 8 Hz. Here 8 Hz corresponds to a Strouhal number (St) of unity. Thus, this result indicates that the flame was in a quasi-steady state when St<1.0 while it became unstable when St>1.0. The variation in flame location and the flame displacement speed did not follow those for the steady state condition and made a limit cycles. This was due to the back support effect. The cycles were significantly inclined at higher frequencies. In the lean condition, the limit cycle was inclined similarly for both the one-step and four-step reaction mechanisms. In the rich condition, however, the limit cycle for the four-step reaction was more inclined than that for the one-step reaction. These results show that the formation of CO and H2 played an important role in the rich condition.